2012
DOI: 10.1186/2045-3701-2-38
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the link between malfunctions in Drosophila neuroblast asymmetric cell division and tumorigenesis

Abstract: Asymmetric cell division is a developmental process utilized by several organisms. On the most basic level, an asymmetric division produces two daughter cells, each possessing a different identity or fate. Drosophila melanogaster progenitor cells, referred to as neuroblasts, undergo asymmetric division to produce a daughter neuroblast and another cell known as a ganglion mother cell (GMC). There are several features of asymmetric division in Drosophila that make it a very complex process, and these aspects wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 90 publications
0
9
0
Order By: Relevance
“…However, given the known role of CtBP in influencing cellular reprograming and antagonizing the epithelial phenotype [118], it is tempting to speculate that this property of CtBP could have a role in defining epithelial polarity [165167]. The partitioning of the Golgi during mitosis may also have a significant role in promoting formation and orientation of the mitotic spindle and thus could influence the asymmetric division necessary for the formation of stratified epithelia and the maintenance of pluripotent stem cell pools [168, 169]. Similar membrane trafficking promoted by CtBP3/BARS may have a role in maintaining the basolateral and apical polarity of epithelial cells during tissue morphogenesis, regeneration, and wound healing.…”
Section: Moonlighting Functions Of Ctbp In the Cytoplasmmentioning
confidence: 99%
“…However, given the known role of CtBP in influencing cellular reprograming and antagonizing the epithelial phenotype [118], it is tempting to speculate that this property of CtBP could have a role in defining epithelial polarity [165167]. The partitioning of the Golgi during mitosis may also have a significant role in promoting formation and orientation of the mitotic spindle and thus could influence the asymmetric division necessary for the formation of stratified epithelia and the maintenance of pluripotent stem cell pools [168, 169]. Similar membrane trafficking promoted by CtBP3/BARS may have a role in maintaining the basolateral and apical polarity of epithelial cells during tissue morphogenesis, regeneration, and wound healing.…”
Section: Moonlighting Functions Of Ctbp In the Cytoplasmmentioning
confidence: 99%
“…6,7 NUMB (protein numb homologue) is the human homologue of the protein numb that was initially discovered in Drosophila melanogaster as an adaptor protein responsible for recruiting proteins into different signalling pathways. 8 NUMB is an evolutionarily conserved protein well-known for its multifaceted role in neurogenesis 9,10 and cellular homeostasis within the peripheral and central nervous systems. 8,11 The antagonistic influence of NUMB on the NOTCH pathway and the associated regulation of cell fate has drawn attention to the potential role of NUMB in tumorigenesis in a number of solid tumours, including those arising in the prostate.…”
Section: Introductionmentioning
confidence: 99%
“…Mutation of proteins regulating the MS orientation in NBs might result in abnormal segregation of cell fate determinants and their adaptor proteins (e.g., Miranda), during telophase (Wang et al , ; Cabernard & Doe, ; Kelsom & Lu, ). We observed that 100% of the examined telophase alix 1 NBs showed normal segregation of Miranda into the future ganglion mother cell (GMC), indicating restoration of the spindle misorientation during telophase (i.e., telophase rescue) (Fig EV1G).…”
Section: Resultsmentioning
confidence: 99%
“…We observed that 100% of the examined telophase alix 1 NBs showed normal segregation of Miranda into the future ganglion mother cell (GMC), indicating restoration of the spindle misorientation during telophase (i.e., telophase rescue) (Fig EV1G). Severe defects in MS misorientation in NBs can result in two daughter cells with NB identity and thus excess NBs (Kelsom & Lu, ; Gonzalez, ). However, we detected approximately the same number of NBs per brain lobe, specifically on average 93 ± 2.7 in wild‐type brains and 100 ± 2.8 in alix 1 mutant brains (Fig EV1H), in accordance with the observed telophase rescue (Fig EV1G).…”
Section: Resultsmentioning
confidence: 99%